The donor–beneficiary charity accountability paradox: a tale of two stakeholders. Issue 3 (16th April 2017) - Connolly, Ciaran; Hyndman, Noel
Abstract : Using stakeholder theory, this paper explores the motivations of charities in discharging accountability and the interplay of donor and beneficiary accountability needs. It considers the extent to which concentration on one group may disadvantage another. The authors found that stakeholders commonly perceived as more salient, such as donors, cede power and impute saliency to beneficiaries.